The stellar orbit distribution in present-day galaxies inferred from the CALIFA survey - Zhu, Ling; Grand, Robert J. J. (Nature astronomy, 2018)
The distribution of circularity of stellar orbits within 300 galaxies of the present-day Universe, with masses between 108.7 and 1011.9 M ⊙, is directly observed by the CALIFA survey and provides a benchmark for galaxy simulations.